Microdeletion/duplication at 15q13.2q13.3 among individuals with features of autism and other neuropsychiatric disorders. Issue 4 (19th September 2008) - Miller, D T; Shen, Y; Weiss, L A; Korn, J; Anselm, I; Bridgemohan, C; Cox, G F; Dickinson, H; Gentile, J; Harris, D J; Hegde, V; Hundley, R; et al.
Abstract : Background: Segmental duplications at breakpoints (BP4–BP5) of chromosome 15q13.2q13.3 mediate a recurrent genomic imbalance syndrome associated with mental retardation, epilepsy, and/or electroencephalogram (EEG) abnormalities. Patients: DNA samples from 1445 unrelated patients submitted consecutively for clinical array comparative genomic hybridisation (CGH) testing at Children's Hospital Boston and DNA samples from 1441 individuals with autism from 751 families in the Autism Genetic Resource Exchange (AGRE) repository. Results: We report the clinical features of five patients with a BP4–BP5 deletion, three with a BP4–BP5 duplication, and two with an overlapping but smaller duplication identified by whole genome high resolution oligonucleotide array CGH. These BP4–BP5 deletion cases exhibit minor dysmorphic features, significant expressive language deficits, and a spectrum of neuropsychiatric impairments that include autism spectrum disorder, attention deficit hyperactivity disorder, anxiety disorder, and mood disorder. Cognitive impairment varied from moderate mental retardation to normal IQ with learning disability. BP4–BP5 covers ∼1.5 Mb (chr15:28.719–30.298 Mb) and includes six reference genes and 1 miRNA gene, while the smaller duplications cover ∼500 kb (chr15:28.902–29.404 Mb) and contain three reference genes and one miRNA gene. The BP4–BP5 deletion and duplication events span CHRNA7, a candidate gene for seizures. However, none of these individuals reported here have epilepsy, although two have an abnormal EEG. Conclusions: The phenotype of chromosome 15q13.2q13.3 BP4–BP5 microdeletion/duplication syndrome may include features of autism spectrum disorder, a variety of neuropsychiatric disorders, and cognitive impairment. Recognition of this broader phenotype has implications for clinical diagnostic testing and efforts to understand the underlying aetiology of this syndrome.